Relações de gênero e sexualidade no cotidiano escolar: concepções de duas professoras do ensino fundamental. - Nunes, Maria Dolores de Figueiredo (2002)
This work has as starting point the question: How do female teachers of first graders at Elementary Schools perceive the construction of their conceptions and experiences concerning, specifically, their work with sexuality and gender relations that are present in classrooms and other school premises ? Its objectives were to identify through interviews with female teachers: a)the perceptions about the course of their professional formation; b) their perceptions about sexuality and gender relations present in the interpersonal relations in the classroom; c) perceptions of ways in which they themselves deal with questions related to gender and sexuality; d) conceptions that enter their perceptions (or their absence) about sexuality and gender relations of their male and female pupils; e) their personal conceptions of sexuality and gender relations that influence their perceptions and conceptions of sexuality in infancy and gender relations; f) how their conception interferes with the relations that they establish with their male and female pupils and which they let these establish with them. To collect data two female teachers of local State schools in São Carlos, State of São Paulo, Brazil, were interviewed. Analyzing their testimony resulted in three thematic focos, which are: the formation and the pedagogical experience; b) the male and female pupils and the female teacher: perception of gender relations present at school; c) sexuality present at school. The results of the research confirmed that the school provides its pupils with Sexual Education, ruled by sexist stereotypes and by hiding the infantile sexuality, as already disclosed by extensive literary work about this subject.. Analyzing the interviews of the female teachers also demonstrated that they perceive that their conceptions originate , to a large extent, in multiple factors, among others, the home education, which they received during infancy, and which was heavily influenced by Christianism, predominantly Catholicism. The media, represented by television, but mainly by magazines for adolescents, also took part in this construction, giving information nor always available through family or friends. The data also revealed that the teachers training courses only superficially approach the human sexuality question without special attention to the infantile sexuality. Moreover, the interviews disclosed that the school educators visualized very little, and in an intuitive and spontaneous way, the sexuality of their male and female pupils, as well as their manifestations. Finally, these female teachers said to believe in the importance and in the necessity of a formal Sexual Education in the school curriculum with teachers specially prepared for this task.